2014
DOI: 10.1128/aac.02653-13
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Genetic Diversity Identified among Sporadic Methicillin-Resistant Staphylococcus aureus Isolates Recovered in Irish Hospitals between 2000 and 2012

Abstract: e Clonal replacement of predominant nosocomial methicillin-resistant Staphylococcus aureus (MRSA) strains has occurred several times in Ireland during the last 4 decades. However, little is known about sporadically occurring MRSA in Irish hospitals or in other countries. Eighty-eight representative pvl-negative sporadic MRSA isolates recovered in Irish hospitals between 2000 and 2012 were investigated. These yielded unusual pulsed-field gel electrophoresis and antibiogram-resistogram typing patterns distinct f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 72 publications
3
33
0
Order By: Relevance
“…Since then, several retrospective and prospective studies using human S. aureus isolates/samples were carried out in order to search for mecC -MRSA isolates ( Table 1 and Table 2 ) [ 16 , 18 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ,…”
Section: Detection Of Mecc -Mrsa Isolates In Humentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several retrospective and prospective studies using human S. aureus isolates/samples were carried out in order to search for mecC -MRSA isolates ( Table 1 and Table 2 ) [ 16 , 18 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ,…”
Section: Detection Of Mecc -Mrsa Isolates In Humentioning
confidence: 99%
“…Importantly, the criteria chosen for the selection of the initial isolates/samples varied significantly. While all S. aureus isolates were collected in some studies [ 29 , 38 , 45 ], only MRSA isolates were included in others [ 24 , 26 , 27 , 28 , 32 , 33 , 36 , 41 , 42 ]. Moreover, several studies were more restrictive and only used isolates that showed characteristics suspected of carrying the mecC gene such as spa types associated with mecC -positive clonal lineages previously described, mecA -negative MRSA isolates, isolates with antimicrobial susceptibility suspected to be mecC -positive or pvl -negative MRSA isolates [ 25 , 26 , 37 , 69 ] ( Table S1 ).…”
Section: Detection Of Mecc -Mrsa Isolates In Humentioning
confidence: 99%
“…These include the distribution of dominant healthcare-associated MRSA (HA-MRSA) in hospitals, which may differ according to the geographic location and time period, 30 the introduction of both community-associated MRSA (CA-MRSA) and livestockassociated MRSA (LA-MRSA) clones in the hospital setting, 14 the emergence of clones carrying Staphylococcal cassette chromosome mec (SCCmec) XI, 22 and extensive genetic diversity among sporadic MRSA isolates. 13 This large variety of clones with their different antimicrobial resistance potential means that information on MRSA clonal distribution in hospitals and the clinical repercussion is essential.…”
Section: Introductionmentioning
confidence: 99%
“…To date, mecC has been identified in S . aureus isolates belonging to the animal-associated CCs 49, 130, 425, 599 and 1943; and mecC MRSA have been isolated from humans, mainly from different Western and Central European countries, but also from diverse animal species including cattle, sheep, hedgehogs, dogs, cats, a harbor seal ( Phoca vitulina ), a guinea pig, rabbits, rats, and a chaffinch ( Fringilla coelebs ) [39,76,86,87,89,90,91,92,93,94,95,96,97,98,99,100,101,102]. Recently, mecC was also identified in veterinary Staphylococcus xylosus [103] and Staphylococcus stepanovicii [104] isolates.…”
Section: Introductionmentioning
confidence: 99%